Pendidikan Agama Islam Berbasis Anti Terorisme di SMA - Wiyani, Novan Ardy (Jurnal Pendidikan Islam, 2013)
“PAI” teachers are required to be able to create a healthy climate of religios to avoid the Islamic radicalism in high school. One effort that can be done by the”PAI” teachers is to practice the de-radicalization of Islamic education through the integration of education values on anti-terrorism in teching-learning of “PAI”. The educational values of antiterrorism that will be integrated in the teching-learning of “PAI” included citizenship, compassion, courtesy, fairness, moderation, respect for the other, respect for the creator, self control, and tolerance. Then, they are integrated into the learning objectives, learning materials, learning experiences, and evaluation of learning.